2015
DOI: 10.1111/febs.13365
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic mutations weaken the interactions that stabilize the p110α‐p85α heterodimer in phosphatidylinositol 3‐kinase α

Abstract: Phosphatidylinositol 3-kinase α (PI3Kα) is a heterodimeric lipid kinase that catalyzes the conversion of phosphoinositide-4,5-bisphosphate (PIP2) to phosphoinositide-3,4,5-trisphosphate (PIP3). The PI3Kα signaling pathway plays an important role in cell growth, proliferation and survival. This pathway is activated in numerous cancers, where the PI3KCA gene, which encodes for the p110α PI3Kα subunit, is mutated. Its mutation often results in gain of enzymatic activity; however, the mechanism of activation by on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 68 publications
1
39
0
Order By: Relevance
“…This calculation was repeated 1,000 times with different random numbers, and the 1,000 values for each individual Cα atom in the chain were averaged (82). We showed that the calculation converges when more than 500 values are averaged.…”
Section: Methodsmentioning
confidence: 99%
“…This calculation was repeated 1,000 times with different random numbers, and the 1,000 values for each individual Cα atom in the chain were averaged (82). We showed that the calculation converges when more than 500 values are averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Larger truncations of C-terminal domains greatly attenuate the effects of the single cSH2 domain deletions, resulting in constructs of low activity for p85α as well as p85β. Interacting with p110, the nSH2 domain binds to the helical domain and the iSH2 domain associates with the adapter-binding and C2 domains of p110 to stabilize and inhibit the catalytic subunit [ 13 , 16 , 18 , 20 , 21 ]. Both SH2 domains play distinct roles in the regulation of PI3K activity [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…PIK3CA is frequently mutated in different types of cancer (Samuels and Waldman, 2010;Mangone, et al, 2012;Wang, et al, 2013;Schmidt, et al, 2018). Anomalies in p110α are associated with increased enzymatic activity of PI3K and promote oncogenesis in affected cells (Bader, et al, 2005;Echeverria, et al, 2015). Due to their roles in promoting cancer cell survival, transformation, proliferation, and migration, PI3Ks are considered promising targets in cancer therapy (Vivanco and Sawyers, 2002;Hausler, et al, 1998;Vanhaesebroeck, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%